Development of a PROM set for patients with Guillain–Barré syndrome (GBS) and chronic inflammatory demyelinating polyneuropathy (CIDP): study protocol - Pelouto, Farah; Haagsma, Juanita. A.; Jacobs, Bart C.; Terwee, Caroline B. (Health and quality of life outcomes, 2025)
Background Guillain–Barré syndrome (GBS) and Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) are rare immune-mediated disorders of the peripheral nervous system. They cause significant physical and mental symptoms and functional impairments that impact patients’ daily lives. Current treatment does not effectively prevent the occurrence of these residual symptoms and functional limitations. Patient-Reported Outcomes (PROs) and Patient-Reported Outcome Measures (PROMs) are essential tools that capture patients’ perspectives on their own health, which can be used to assess disease impact and evaluate treatment efficacy. The commonly used Inflammatory Rasch-Built Overall Disability Scale (I-RODS) primarily focuses on activity limitations, social participation, but has been noted to have certain clinimetric shortcomings. This highlights the need for a tailored PROM set that comprehensively assesses relevant aspects of health-related quality of life (HRQL) in patients with GBS or CIDP. Methods This prospective mixed-method study consists of a multiphase approach for developing a PROM set in a Dutch adult population with GBS and CIDP. The first phase involves a systematic review and an (online) survey with open-ended questions to identify relevant patient-reported outcomes (PROs), which will be analyzed qualitatively. Subsequently, stakeholder panel meetings will be held with patients and healthcare providers to discuss the identified PROs, including generic and disease specific symptoms and existing suitable PROMs, using the generic Patient Reported Outcomes Measurement Information System (PROMIS) as a basis. Following this, cognitive interviews will be performed to pilot-test a new disease-specific symptom checklist. A Delphi study will then be conducted to achieve consensus on the final PROM set. Finally, a validation study of the selected PROMIS measures and the newly developed disease-specific symptom checklist will be performed. The final phase of the study involves a consensus meeting with the stakeholders to discuss dissemination and implementation strategies for the proposed PROM set. Discussion This PROM set is being developed to measure HRQL outcomes relevant for patients with GBS and CIDP. The aim is to develop a tool for clinical practice and research to evaluate the clinical course and effect of treatments from the perspective of patients. Trial registration Not applicable.